The Edgerton Structure: A Possible Meteorite Impact Feature in Eastern Kansas - Daniel F. Merriam; Jianghai Xia; John W. Harbaugh (International Journal of Geophysics)
Recognized meteorite impact features are relatively rare in the U.S. Midcontinent region, but recently with increased interest and research, the number has increased dramatically. We add another possibility to the growing list, the Edgerton structure in northwestern Miami County, Kansas. The feature is elliptical (∼5.5 × 6.5 km, slightly elongated east-west) with radial surface drainage. The feature was first observed on hillshade maps of digitized topography of 7.5 minute quadrangles. Subsequent magnetic profiles show a higher magnetic value in the center of the ellipse with higher values around the edges; this shape is characteristic of an impact feature. Depth to the anomalous body is estimated to be about 1 km, which puts it in the Precambrian crystalline basement under a cover of Paleozoic sediments. There are no deep boreholes in the vicinity and no seismic profiles are available. If it is an impact structure, it will be the second such feature documented in Kansas, the first being the Brenham meteorite crater at Haviland in Kiowa County in southwestern Kansas. It would be older than the other impact structures identified in the Midcontinent—Manson in Iowa, Ames in Oklahoma, Haswell Hole in Colorado, and possibly Belton in Missouri and Merna in Nebraska. There are at least two other prospective impact features in Kansas: the Goddard ring west of Wichita and Garden City ellipse north-west of Garden City.